Implementasi Kebijakan Perlindungan Perempuan Korban Kekerasan Dalam Rumah Tangga Di Kota Merauke - Eko Rachmat Saputro; Natalia Suryani Purba; Nur Jalal; Muhammad Adrian (PAPSEL RESEARCH AND CONSULTANT, 2025)
The struggle of women to achieve prosperity and justice, which has been carried out for a long time, has not been able to raise the dignity of women to be equal to men. Law number 23 of 2004 concerning the elimination of domestic violence very clearly mandates that every act against someone, especially women, which results in violence or physical, sexual, psychological suffering and/or domestic neglect includes threats to commit acts, coercion, or unlawful deprivation of liberty within the domestic sphere. This research aims to analyze the implementation of policies to protect women victims of domestic violence in Merauke City. The method used in this research uses a qualitative approach to explore an in depth understanding of this phenomenon, with data sources in the form of primary and secondary data. Primary data was obtained through in-depth interviews with relevant informants, while secondary data was obtained from supporting documents related to policies and their implementation. Data collection was carried out through observation, interviews, and documentation. Data analysis was done using Miles and Huberman's interactive approach, including data reduction, presentation, and conclusion. Results of this research The results of the study show that the implementation of the policy to protect women victims of domestic violence in Merauke Regency faces several challenges, including limited human resources and facilities. Still, collaborative efforts between the regional government and local communities have positively contributed to its implementation. This research recommends that related parties increase policy effectiveness by strengthening institutional capacity, public awareness, and cross-sector collaboration. Thus, it is hoped that this research can improve women's protection services and policies in Merauke Regency